The Development of an Android-Based Dictionary for Blind - Susilowati, Novi Eka; Syafi'i, Imam; Aftina, Aftina; Syahrul, Azzhan; Nogroho, Dwi Prasetyo; Bitari, Sekar (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This study aims to develop an Android-based Indonesian dictionary for the blind. This study was developed using the Borg & Gall development model with some adjustments to the needs of this study. The stages of product development are (1) preliminary studies, (2) planning, (3) product development, (4) product validation, (5) first phase revision, (6) trials, (7) second phase revision, and (8) dissemination. The product developed is an android-based dictionary application with voice input and output. This developed product has been validated and tested on a small scale. Validation is carried out for material expert validators, media experts, and practitioners; while small-scale trials were conducted on 5 people with visual impairments. The results of product validation and trial show that the product developed is feasible to be implemented with an average percentage rating of 91.93%. The product developed provides benefits to the blind, which makes it easier to understand the meaning of words in the dictionary and increases the independence of the blind.